Pemilihan Kepala Daerah (Pilkada) dan Tantangan Demokrasi Lokal di Indonesia - Suyatno, Suyatno (Political Science Program, Universitas Negeri Semarang, 2016)
Direct local leader elections (Pilkada) had replaced indirect local elections. It based on the spirit of people empowerment to participate choosing local leaders more democratic. Responsiveness is an important element besides participation which represent local democracy. These two variables will decide the local elections that can enhance the quality of local democracy. This paper uses qualitative methodology to analyze the data of participation and responsiveness of Pilkada as an important variables in local democracy. People participation in Pilkada is not as high as the participation in New Order elections. Their participation are more substantive because accompanied assessment of the level of responsiveness of a local leader. Incumbent successful running of local responsiveness will get continued success as the next local elections victory. In contrast, incumbent who failed in the implementation of responsiveness will obtain defeat. Victory and defeat incumbent in the election can be stated that the relevance of participation and responsiveness become very important in the local democratic process as a whole.